Pathogenicity Of Pasteurella Multocida Serotypes A:3, D:1 And D:3 In Rabbits - Al-Haddawi, Muthafar Hussain (1999)
Eighty-two isolates of P. multocida were recovered from healthy and diseased rabbits in a rabbitry at Universiti Putra Malaysia. S ixty three isolates were obtained from adult rabbits and 1 9 isolates were from juvenile rabbits. Bacterial identification by biochemical tests, capsular and somatic serotyping and sensitivity to the antimicrobials were conducted. Capsular typing revealed that the major capsular type was type A (89%), while type D was less frequent ( 1 1 %). Somatic serotyping of 46 isolates showed that serotypes 1 and 3 were more frequent among the capsular types. Most isolates were sensitive to several common antimicrobials but some were resistant to neomycin, penicillin, cloxacillin and tetracycline. Six of 40 isolates of P. multocida from healthy ( 1 8 isolates) and diseased (22 isolates) rabbits were found to harbour plasmids. There was no correlation between presence of plasmids and serotype, resistance to antimicrobial agents and from the site which the bacteria were cultured. Random amplification polymorphic DNA (RAPD) was applied to subtype 40 P. multocida isolates using two single primers to test their abilities to generate individual fingerprints. A wide heterogeneity within the isolates was observed. Sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) of the 40 isolates revealed over 40 protein bands with high molecular weight bands indicating striking homogeneity among the isolates. Twenty-two different patterns were observed.